Development of a minimal invasive and controllable murine model to study polymicrobial abdominal sepsis. Issue 1 (1st January 2021) - Steinhagen, Folkert; Hilbert, Tobias; Cramer, Nina; Senzig, Sebastian; Parcina, Marijo; Bode, Christian; Boehm, Olaf; Frede, Stilla; Klaschik, Sven
Abstract : Sepsis, a life-threatening organ dysfunction, continues to cause considerable morbidity. Reliable animal models to evaluate therapeutic options are urgently required, however, some of the most established ones are technically challenging. We herein present a murine model of abdominal sepsis based on the intraperitoneal (i.p.) injection of a defined inoculum of stool specimens (IPSI). Fecal bacterial compositions of male C57BL/6N mice were used for experiments. Dilutions of suspended stool (1:3, 1:6, 1:9) were injected i.p. into recipient mice. Clinical symptoms, cytokine expression, and mortality were assessed up to 48 h following IPSI. Storage at 4°C for 72 h exerted only minimal effect on bacterial composition, while deep freezing substantially impacted bacterial viability. After 9 h following IPSI, a dose-dependent, significant increase in clinical score was visible in all stool-injected mice. The same was observed for expression levels of pro-inflammatory cytokines IL-6 and CCL-2. Mortality rate of septic mice ranged from ∼30% (1:9) to 100% (1:3) within 48 h, depended on the dilution of stool inoculum. The IPSI model ensures experimental stability while mimicking a pathophysiological relevant stimulus similar to other established models. Characterization of microbial composition, minimal invasiveness and easy technical handling allow a good reproducibility and disease severity can be titrated.